P-wave duration and interatrial block as predictors of new-onset atrial fibrillation: A systematic review and meta-analysis - Konstantinos Zagoridis; Emmanuel Koutalas; Stergios Intzes; Marianthi Symeonidou; Nikoleta Zagoridou; Konstantinos Karagogos; Emmanuel Spanoudakis; Emmanuel Kanoupakis; George Kochiadakis; Borislav Dinov; Nikolaos Dagres; Gerhard Hindricks; et al. (Hellenic Journal of Cardiology, 2023)
Background: Early detection of atrial fibrillation (AF) could improve patient outcomes. P-wave duration (PWD) and interatrial block (IAB) are known predictors of new-onset AF and could improve selection for AF screening. This meta-analysis reviews the published evidence and offers practical implications. Methods: Publication databases were systematically searched, and studies reporting PWD and/or morphology at baseline and new-onset AF during follow-up were included. IAB was defined as partial (pIAB) if PWD≥120 ms or advanced (aIAB) if the P-wave was biphasic in the inferior leads. After quality assessment and data extraction, random-effects analysis calculated odds ratio (OR) and confidence intervals (CI). Subgroup analysis was performed for those with implantable devices (continuous monitoring). Results: Among 16,830 patients (13 studies, mean 66 years old), 2,521 (15%) had new-onset AF over a median of 44 months. New-onset AF was associated with a longer PWD (mean pooled difference: 11.5 ms, 13 studies, p < 0.001). The OR for new-onset AF was 2.05 (95% CI: 1.3-3.2) for pIAB (5 studies, p = 0.002) and 3.9 (95% CI: 2.6-5.8) for aIAB (7 studies, p < 0.001). Patients with pIAB and devices had higher AF-detection risk (OR: 2.33, p < 0.001) than those without devices (OR: 1.36, p = 0.56). Patients with aIAB had similarly high risk regardless of device presence. There was significant heterogeneity but no publication bias. Conclusion: Interatrial block is an independent predictor of new-onset AF. The association is stronger for patients with implantable devices (close monitoring). Thus, PWD and IAB could be used as selection criteria for intensive screening, follow-up or interventions.